Congenital aplasia of cartilaginous nasal septum: A case report - Rani Hammoud (17823404) (2022)
Congenital absent cartilaginous septum is an extremely rare condition. We are presenting a case of a 46 years-old female patient who presented with intermittent episodes of epistaxis, physical examination and radiology confirmed the lack of cartilaginous nasal septum. Other Information Published in: Otolaryngology Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.xocr.2022.100488